Concept of Distance Learning In University - Project Organization and Management - Vladimir Valentinovich Aleskovskiy; Tatiana Anatolievna Pavlova; Valery Vitalyevich Yanovskiy (Управленческое консультирование)
One of the necessary conditions for formation and development of a unified open educational space is the improving the system of distance learning. This paper analyzes the basic concepts and features of distance learning as a form of self-organization of learning on IT basis, its different aspects. Also, the basic approaches to e-learning, especially in the Russian practice of distance education, the minimum requirements for the content of e-learning discipline are considered. It is shown that the benefits of distance learning outweighed his shortcomings, and therefore this form of learning are very useful for our country where transport infrastructure are not comfortable in generally.